The Domestic Violence Screening Through The Empowerment of Mental Health Cadres - Erawati, Erna; Triredjeki, Hermani; Sunarmi, Sunarmi; Isworo, Adi; Sarwono, Bambang (Universitas Negeri Semarang, 2018)
Domestic violence spans across cultures and many countries include Indonesia. In the women and children perspectives, it is taboo to report the domestic violence because it is a private matter, not for the public domain. Therefore domestic violence screening through the empowerment and mentoring of mental health cadres is needed to raise awareness of domestic violence in rural community. The aim of this study is to explore the influence of the empowerment and mentoring of mental health cadres on screening domestic violence. A quasi experimental was conducted among mental health cadres. The total sampling derived from six sub district of Kalegen village. Data were analyzed by using SPSS (version 19). A total sample of 22 mental health cadres aged between 28 years to 49 years. There is a high significant screening capability in pretest-posttest after empowerment andÃ‚Â mentoring of mental health cadres (p> .001). The empowerment and mentoring of mental health cadres on screening domestic violence could strengthen support and raising domestic violence awareness. This intervention should become a part of community health program in community. A longitudinal study can be carried out to prevent domestic violence.